The Effect of Business strategy on Innovation capability, Absorptive capacity and Performance of SMEs in Pakistan - Arshad, Muhammad Zulqarnain; Arshad, Darwina (2017)
Small and medium enterprises (SMEs) play a vital role in the development of the economy of any country. In Pakistan SMEs hold about 90 percent of the total businesses.The performance of SMEs depends upon many factors.The purpose of this study is to investigate the relationship between Innovation Capability, Absorptive Capacity and Performance of SMEs in Pakistan.This conceptual paper also extends to the vague revelation on Business Strategy in which act as a moderator between Innovation Capability, Absorptive Capacity and Performance of SMEs.Conclusively, this study proposes a new research directions and hypotheses development to examine the relationship among the variables in the context of SMEs in Pakistan.